Dynamics of retinal changes in early-stage Parkinson’s disease - Ane Murueta-Goyena; Sara Teijeira-Portas; Elisa Blanco Martín; Raquel Vázquez-Picón; Blanca Ruiz Bajo; Jone Bocos; Jorge Sánchez-Molina; Patricia Alves Dias; Ioana Croitoru; Iñaki Rodríguez Agirretxe; Rocío Del Pino; Marian Acera; et al. (Acta Neuropathologica Communications, 2025)
Abstract Parkinson’s disease (PD) is a neurodegenerative disorder primarily characterized by motor symptoms, with emerging evidence suggesting retinal pathology, particularly in the ganglion cell-inner plexiform layer (GCIPL), detectable via optical coherence tomography (OCT). This study aimed to characterize early retinal dynamics in PD using OCT. We conducted a prospective one-year longitudinal multicenter study involving 53 early-stage PD patients with a disease duration of 5 years or less and 52 controls. The participants underwent retinal spectral-domain OCT, primary visual function and cognitive examinations. We examined baseline retinal measures and short-term longitudinal differences between groups via linear mixed effects models. In PD patients, the baseline GCIPL thickness in central regions was increased by up to 4 μm, and the rate of thinning in the parafoveal GCIPL was − 0.61 [0.29] µm/year faster over a one-year follow-up period than in controls in the 2- to 3-mm ring (p = 0.039). In PD patients, greater central GCIPL thickness was associated with poorer contrast sensitivity and reduced performance on the Farnsworth D15 color vision test. It also predicted subsequent thinning in both the GCIPL (2- to 3-mm ring) and the inner nuclear layer (2- to 5-mm rings). However, this increased thickness was not linked to prevalent or progressive motor or cognitive manifestations. In conclusion, this study provides the first detailed topographical description of early retinal dynamics in PD patients, revealing increased central GCIPL thickness and accelerated parafoveal GCIPL thinning in PD. However, the macular region shows complex and variable dynamics among PD patients, but these changes precede detectable progression in clinical scales.